Faktor-Faktor yang Berhubungan dengan Kejadian Coronavirus Disease 2019 (COVID-19) di Provinsi Jawa Tengah - Rahmita Damayanti; Dwi Sutiningsih; Nissa Kusariana; Retno Hestiningsih (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is a global pandemic disease which attacked respiratory organ and caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Central Java is the third-ranked province with the most positive COVID-19 cases in Indonesia and is still experiencing additional cases until December 2021. Central Java has also been the province with the highest number of COVID-19 red zones in Indonesia. Factors related to COVID-19 have to be known so the efforts to prevent COVID-19 can be carried out effectively and the risks of infection can be decreased. This study aims to analyze the factors related to COVID-19 infections of Central Java population.Methods: This research is an analytical study with a cross sectional approach. The research method is quantitative. The research samples were 200 citizens of Central Java Province. The sampling technique was proportional to size sampling. This study used a questionnaire for data collection.Result: The results of the research show that the factors related to COVID-19 infections are sex (p-value = 0.007), smoking status (p-value = 0.017), comorbidity status (p-value = 0.000), alcohol consumption behavior (p-value = 0.000), and preventive practice of COVID-19 (p-value = 0.001).Conclusion : It can be concluded that sex, smoking status, comorbidity status, alcohol consumption behavior, and preventive practice of COVID-19 are factors related to COVID-19 infections.